Presence of disseminated tumor cells in bone marrow correlates with tumor stage and nodal involvement in cervical cancer patients. Issue 4 (14th September 2013) - Fehm, Tanja; Banys, Malgorzata; Rack, Brigitte; Jäger, Bernadette; Hartkopf, Andreas; Taran, Florin‐Andrei; Janni, Wolfgang
<x xml:space="preserve">Abstract</x> Detection of disseminated tumor cells (DTCs) in the bone marrow (BM) of breast cancer patients is associated with poor outcome. The aim of our study was to evaluate the impact of BM status on survival in a large cohort of cervical cancer patients. Three hundred twenty‐five patients with cervical cancer were included into this prospective two‐center study (University Hospitals Tuebingen, Munich, Germany). BM was collected preoperatively. DTCs were identified by immunocytochemistry using the pancytokeratin antibody A45B/B3. DTCs were detected in 22% of all BM aspirates. The number of CK‐positive cells ranged from 1 to 93 per 2 × 106 mononuclear cells. Eighteen percent of patients with T1 stage presented with DTCs in BM compared to 30% in T2 and 45% in T3/4 patients. Among nodal negative patients, 18% had tumor cells in BM compared to 32% of nodal positive patients. Positive DTC status was associated with tumor size (p = 0.007) and nodal status (p = 0.009) but not with grading (p = 0.426). DTC status did not correlate with overall or disease‐free survival. In the univariate analysis, tumor stage, nodal status, resection status and grading correlated with OS and DFS. In the multivariate analysis, only tumor stage and nodal status were independent predictors of OS and tumor stage, nodal status and grading of DFS. Tumor cell dissemination into BM is thus a common phenomenon in cervical cancer and correlates with higher tumor load but lacks prognostic relevance. Alternative detection methods may be needed to establish prognostic potential.